Hadith Commentary on Popular Islamic Website in Indonesia: Methodology, Discursive, and Social Practices - Tarmizi Tarmizi; Ayu Ariska; Muhammad Fajri; Sukiyat Sukiyat (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2025)
This study examines the methodology of hadith commentary on two prominent Indonesian Islamic websites: hadispedia.id and markazsunnah.com, and analyses the discursive and social practices embedded within such commentary, employing Norman Fairclough's critical discourse analysis (CDA) as its analytical framework. Using a qualitative approach that integrates purposive content analysis, classical hadith commentary methodology (tahlili–ijmali–muqarin typology), and Fairclough's three-level CDA model (text, discursive practice, social practice), the study identifies distinct and internally coherent methodological tendencies at each platform. Hadispedia.id applies the tahlili (analytical) method for hadith on legal themes and the ijmali (synoptic) method for hadith on ethics, consistently contextualising commentary in accessible language suited to a diverse, multi-platform readership. Markazsunnah.com applies the tahlili method consistently across all themes, drawing on classical commentary sources in a systematic scholarly structure suited to a scholarly-oriented readership. At the level of discursive practice, differences in the institutional backgrounds of site administrators, digital distribution ecologies, and modes of reader engagement are shown to shape methodological choices and presentational styles. At the level of social practice, digital hadith commentary serves as a tool for sharing Islamic teachings, promoting mainstream Islamic beliefs, negotiating academic authority in the online religious space, and building social connections through regular interaction with audiences. The study finds that digital hadith commentary is not a neutral platform; instead, it actively influences the way hadith scholarship is understood and creates idealised views of the Muslim audience. This study advances the literature on contemporary hadith scholarship by offering an integrated analytical procedure bridging classical Islamic methodology and CDA to illuminate the socio-religious implications of digital hadith dissemination.